CFD based erosion modelling of abrasive waterjet nozzle using discrete phase method - Naqib Hakim, Kamarudin; A. K., Prasada Rao; Azmir, Azhari (IOP Publishing, 2016)
In Abrasive Waterjet (AWJ) machining, the nozzle is the most critical component that influences the performance, precision and economy. Exposure to a high speed jet and abrasives makes it susceptible to wear erosion which requires for frequent replacement. The present works attempts to simulate the erosion of the nozzle wall using computational fluid dynamics. The erosion rate of the nozzle was simulated under different operating conditions. The simulation was carried out in several steps which is flow modelling, particle tracking and erosion rate calculation. Discrete Phase Method (DPM) and K-ε turbulence model was used for the simulation. Result shows that different operating conditions affect the erosion rate as well as the flow interaction of water, air and abrasives. The simulation results correlates well with past work.